Interactivity in VR Therapy : Assessing Efficacy Across Acrophobia Severity - Chan, Chiew Mei; Chai, Soo See; Goh, Kok Luong; Sim, Sze Kiat (Science Publications, 2025)
Virtual Reality (VR) and Artificial Intelligence (AI) have gained popularity in medical treatments, including for acrophobia- a common but often untreated fear of heights. Traditional therapies are often expensive and complex, making VR therapy a convenient and safe alternative. This study evaluates the efficacy of an AI-augmented interactivity VR therapy for acrophobia, focusing on user satisfaction and treatment outcomes. Graded exposure VR therapy was used where participants were gradually exposed to VR environments tailored to their severity levels of acrophobia, guided by an AI agent based on the Behavioral Avoidance Test (BAT). Participants engaged in interactive tasks such as collecting flowers or coins, enhancing immersion and reducing anxiety. The participants were included based on the visual Height Intolerance Severity Scale (vHISS), which measured posttherapy fear levels with the Attitudes Towards Heights Questionnaire (ATHQ). Results showed a significant decrease in anxiety levels, with ATHQ scores dropping by an average of 25% across all severity groups (p<0.05). These findings suggest that AI-augmented VR therapy is a promising tool for treating acrophobia. Future research should explore optimizing interactivity to maximize therapeutic effectiveness for various severity levels.